UJI EFEKTIVITAS SALEP EKSTRAK ETANOL DAUN BUNGA KERTAS (BOUGAINVILLEA GLABRA) TERHADAP LUKA EKSISI PADA TIKUS JANTAN PEMBANDING POVIDONE IODINE SALEP - Delisma Simorangkir (Jurnal Penelitian Farmasi & Herbal, 2022)
The wound is a physical injury that results in tears and damage to skin tissue. One type of wound is excision wound, excision wound is of the a wound that is caused by cutting tissue by sharp object scratches. The main goal in wound management is to achieve rapid healing with optimal function and good results. That can be achieved by preventing further infection and trauma with the availability of an environment that can optimize the healing of the wound. One plant that has the potential to heal wounds is the paper petal plant. The purpose of thes study is to find out the effectiveness of giving paper petal extract to the healing of excision wounds in male rats. The study conducted in the Laboratory Health Institute of the Deli Husada Deli Tua. The extracts formulated into ointment preparations with concentrations of 10%, 15%, and 20% then conducted evaluation of ointment preparations, namely organoleptic tests, homogeneity tests, ph tests, visicosity tests, hedonic tests and spread power tests. The results of organoleptic tests and irritant tests of paper petal ethanol extract ointment preparations, all concentrations were declared good while in the most preferred hedonic test was a concentration of 10%. From the results of the spread test is a concentration of 15% with a static test value on the 21st day which is 6.3000 where this value is equal to the value of povidone iodine, while in the pH test on the 21st day the concentration that sees the best statistic test value is 10% concentration with a value of 6.4467 which is close to the value of povidone iodine which is 7.3133. The results of the study is each treatment group experienced a decrease in the diameter of the cut wound. Of the 5 treatment groups, the best reduction in the diameter of the cut wound was the positive control group (povidone iodine) and the 20% concentration where the statistic test value on the 15th day was 0.0000 where this value was equal to the value of povidone iodine.